Race and Right‐Wing Authoritarianism: How Scoring High in Authoritarianism Does Not Necessarily Lead to Support for Right‐Wing Candidates*. (31st May 2016) - Dusso, Aaron
Abstract : Objectives: Authoritarianism has a long history suggesting that it is primarily a phenomenon of the right. However, I argue that this has led to scholars overlooking the potential that, in some contexts, authoritarianism can lead to support for left‐wing candidates. African‐American voters in the United States provide such a context. A key component of right‐wing authoritarianism is that individuals will support whom they believe to be their rightful leader. In the United States, who one believes to be their group's rightful leader is contingent on the race of the voter and the party of the candidate. I hypothesize that as African‐American voters' level of authoritarianism increases, they will be more likely to support the left‐wing Democratic candidate. Methods: I test this hypothesis with a national sample of voters after the 2012 U.S. presidential election. I estimate multiple logit models predicting the probability of voting for Obama, the key independent variables being respondents' right‐wing authoritarian score, their race, and the interaction of these two variables. Results: The results present strong support for my hypothesis that an increase in right‐wing authoritarianism increases the probability of African‐American voters choosing Obama. Conclusion: The results show that the effect of authoritarianism on vote choice is contingent on race/ethnicity. Too often, scholars have overlooked the potential that whom individuals deem to be their established authority is contingent on the political context. These results challenge scholars to provide a more nuanced approach to how authoritarianism influences behavior.